2014
DOI: 10.1007/s00253-014-5991-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable conversion of coffee and other crop wastes to biofuels and bioproducts using coupled biochemical and thermochemical processes in a multi-stage biorefinery concept

Abstract: The environmental impact of agricultural waste from the processing of food and feed crops is an increasing concern worldwide. Concerted efforts are underway to develop sustainable practices for the disposal of residues from the processing of such crops as coffee, sugarcane, or corn. Coffee is crucial to the economies of many countries because its cultivation, processing, trading, and marketing provide employment for millions of people. In coffee-producing countries, improved technology for treatment of the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 65 publications
1
40
0
1
Order By: Relevance
“…Potato flavor also may be detected during processes such as harvesting, transport from harvesting to washing stations, pulping, and fermentation (Hughes et al., ). In this study, earthy odor was found in all samples (No1 to No5) resulting from soil contamination associated with bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Potato flavor also may be detected during processes such as harvesting, transport from harvesting to washing stations, pulping, and fermentation (Hughes et al., ). In this study, earthy odor was found in all samples (No1 to No5) resulting from soil contamination associated with bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the coefficient E472/664 is associated with the level of condensation of the chain of aromatic carbons. Higher values at this coefficient indicate the presence of more aliphatic structures and less aromatic structures[3942]. To further study the functional groups associated with humic substances, FT-IR analysis was performed, and the results are presented in Fig6.…”
Section: Resultsmentioning
confidence: 99%
“…El agua es esencial para todas las formas de vida y en relación con el planeta, América Latina dispone de abundantes recursos naturales incluyendo grandes reservorios hídricos que sustentan en gran medida las amplias expectativas para el desarrollo bioeconómico de la región destacada por su gran producción de productos agrícolas para el mundo, donde el café representa el rubro más comercializado, luego del petróleo, con Brasil al frente como el mayor productor/ exportador a nivel mundial (Malavé y Maza, 2015); donde el agua conforma el recurso fundamental en la agroindustria cafetalera, la cual es crucial para la economía de muchos países Latinoamericanos al proporcionar empleo a millones de personas que participan en su cultivo, procesamiento, comercialización y mercadeo (Hughes et al, 2014).…”
Section: Introductionunclassified